Conducting Qualitative Research on Stigmatizing Conditions With Military Populations. (1st October 2016) - Lincoln, Martha L.; Ames, Genevieve M.; Moore, Roland S.
ABSTRACT: This article addresses the conduct of qualitative research regarding sensitive or stigmatizing topics with military populations, and provides suggestions for implementing culturally responsive and effective data collection with these groups. Given high rates of underreporting of sensitive and stigmatizing conditions in the military, qualitative methods have potential to shed light on phenomena that are not well understood. Drawing on a study of U.S. Army National Guard personnel by civilian anthropologists, we present lessons learned and argue that the value of similar studies can be maximized by culturally responsive research design.